INCREASING STUDENT LISTENING COMPREHENSION USING STORYTELLING: AN ACTION RESEARCH AT THE SECOND YEAR OF SMK HARAPAN KARTASURA - MURJANI, WAHYU TRI (2010)
This research paper is aimed at describing the process of teaching listening using storytelling at the second year of SMK Harapan Kartasura. A preliminary observation in this research showed that the mastery of English listening of the students was still low, because the students's score in the listening test was also low. The students have less motivation to follow the listening lesson. They don't like the English listening lesson, because they think that the listening lesson makes them bored and that material is not interesting. The source of data is teaching learning process using storytelling at second year of SMK Harapan Kartasura, and documents. In this research, the writer does the classroom observation and interview to the English teacher. This research is done on 17 until 24 May 2010.This research is an action research in which the data are taken from interview, observation, event, and documents. The techniques of collecting data are interview, documentation, observation and test for the students. Based on the data analysis, the writer finds that the result of teaching listening using storytelling of the second year students of SMK Harapan Kartasura are as follows: 1). Teaching listening using storytelling at the second year of SMK Harapan Kartasura can improve the students's listening comprehension, because storytelling makes the students become enthusiastic to follow the listening lesson, 2). The writer used picture of the story to motivate the students; 3). The score in the listening test always increase from cycle to cycle. Therefore, the result of teaching listening using storytelling is satisfying.